A novel photo‐acid generator bound molecular glass resist with a single protecting group. Issue 9 (7th February 2013) - Kasai, Tatsuaki; Higashihara, Tomoya; Ueda, Mitsuru
Abstract A novel photo‐acid generator (PAG) bound molecular glass photoresist with a single protecting group has been developed as a promising resist material for use in microelectronics. This single component molecular resist was prepared in four steps starting from 9, 9‐bis(4‐hydroxyphenyl)fluorene. The single component molecular resist exhibited good thermal properties, such as a 10% weight loss temperature of 200 °C and a glass transition temperature of 91 °C. This resist showed a good sensitivity of 60 μC/cm2 with e‐beam exposure (50 keV). On the other hand, the fine pattern with a half‐pitch of 50 nm in the presence of 4 wt % quencher, trioctylamine, was obtained using electron‐beam (100 keV) lithography. The LER value was 8.2 nm (3σ, 60 nm half‐pitch patterns). © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013